Modification and Testing of Replaceable Drum Multi-Crop Thresher - Abagisa, Hussen; Tesfaye, Teka; Befikadu, Dubale (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2015)
In order to help small scale agriculture increase its contribution ensure food security, threshing operation and its subsequent loss followed